Hydroxytyrosol recovery from olive pomace: a simple process using olive mill industrial equipment and membrane technology - Maria F. C. Romeu
In this work, pilot-scale nanofiltration was used to obtain aqueous solutions rich in hydroxytyrosol and tyrosol from olive oil by-products. A large-scale simple process involving olive mill standard machinery (blender and decanter) was used for the olive pomace pre-treatment with water. The aqueous extract was then directly fed to a nanofiltration unit and concentrated by reverse osmosis. Final concentration factors ranged between 7 and 9 for hydroxytyrosol and between 4 and 7 for tyrosol. The final aqueous solution, obtained as retentate stream of reverse osmosis, was highly concentrated in hydroxytyrosol and tyrosol and their concentrations remained stable over at least 14 months.